ANALISIS TROJAN DAN SPYWARE MENGGUNAKAN METODE HYBRID ANALYSIS - Annisa Rizky Damanik; Henki Bayu Seta; Theresiawati Theresiawati (Jurnal Ilmiah Matrik, 2023)
Malicious Software or malware is software created to damage a computer system. The increase in internet users is also in line with the increase in the use of software. However, there are still many users who still use pirated software because it is relatively free and easy to obtain. Pirated software is usually embedded with dangerous malware such as Trojans and spyware. All crimes of spreading this malware are always related to stealing credit card information, internet banking and other cybercrimes. To prove that the software installed and used on a computer is malicious software, digital forensics is required by analyzing the software. Hybrid analysis technique is a combination of static and dynamic analysis which is suitable for analyzing malware activity. Based on the results of the analysis that has been carried out, the ryuk.bin trojan has evolved and the malware forms new malware files when it is run and also changes and destroys the original files on the system.